PROVISION OF EDUCATION AND ASSISTANCE TO PREVENT COVID-19 FOR CITIZENS SEMANGAT BAKTI OF THE BARITO KUALA REGENCY - Mira Mira (UMBanjarmasin, 2021)
The COVID-19 pandemic caused by the coronavirus (SARS-Cov-2) continues to transform world health with worldwide transmission rates reaching the point where one infected person in turn only infects one other person. Community members of the spirit of devotion are in densely populated areas with insufficient levels of compliance with health protocols, thus creating a susceptibility to transmission. Seeing this condition, it is very important for members of the community to have a devoted spirit to protect themselves and their families so as not to contract the COVID-19 disease. Therefore, the team carried out education to increase the knowledge of the community in the spirit of dedication so that they could face and pass the COVID-19 pandemic and the team also provided COVID-19 prevention assistance to overcome the limited means of prevention in the community.